Changes in the quality of palm oil mill effluent (POME) under aerobic treatment - Gilbert Kalaween, Anak Mangga (Universiti Malaysia Sarawak (UNIMAS), 2012)
Malaysia is a rapid growing country. The economy of Malaysia is mostly depends on production of palm oil. However, the production of crude palm oil will also give side effect which is the Palm oil mill effluent (POME). This type of product can pollute our environment. Therefore, the palm oil mill waste management must know how to treat the POME before it is being discharged. POME has high BOD, COD, Oil and Grease, TSS and VSS value. In this project, the raw POME was subjected into 550C temperature and the sample was aerated by using air pump. The POME that had been subjected into that condition is monitored in its quality changes for four consecutive weeks. Parameters such as BOD, COD, Oil and Grease, TSS and VSS have been conducted. The pattern for the changes of BOD, COD and Oil and Grease is decreasing with time. As the time increased, the value of BOD, COD and Oil and Grease decreased. However, for TSS and VSS, both of it show increase in value as the time increased.